Avaliação das principais t́cnicas para obtenção de MPPT de paińis fotovoltaicos - De Brito, Moacyr A.G. [UNESP]; Luigi, G. [UNESP]; Sampaio, Leonardo P. [UNESP]; Canesin, Carlos A. [UNESP] (My University, 2010)
Electrical energy from photovoltaic panels (PV) has became an increasing viable alternative because of the great concern for environmental preservation and the possibility of the reduction of the conventional fuels, and this natural energy source is free, abundant and clean. In addition, Brazil is a privileged country because of the high levels of irradiation throughout its territory all over the year. Thus the exploitation of the energy from PV is one of the best alternatives to overcome the supply electrical energy issues. However, nowadays the energy conversion efficiency is low and the initial costs are high for these energy systems. Therefore, in order to increase the efficiency of these systems the extraction of the maximum power point (MPP) from PV is extremely necessary, and it is done using the maximum power point tracking (MPPT) techniques. The MPP of the PV varies non linearly with the environmental conditions and several MPPT techniques are available in literature, and this paper presents a careful comparison among the most usual techniques, doing meaningful comparisons with respect to the amount of energy extracted, PV voltage ripple, dynamic response and use of sensors, considering that the models are implemented via MatLab/Simulink®. © 2010 IEEE.
Keywords: Energy Efficiency; MPPT Techniques; Photovoltaic Panels; Solar Energy; Conventional fuel; Electrical energy; Energy systems; Environmental conditions; Environmental preservation; Initial costs; MATLAB /simulink; Maximum power point; Maximum power point tracking; Natural energy sources; Photovoltaic panels; Voltage ripples; Conversion efficiency; Dynamic response; Energy efficiency; Photovoltaic effects; Pumps; Solar energy